POLITIK HUKUM PERUNDANG-UNDANGAN - Mattalatta, Andi (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
A law state which decided to be a welfare state gives consequences that inadapted the rules would provide guarantee to all nations and individualsagainst any unfair treatments and arbitrary actions. The law must protectall citizens to their citizen rights and human rights guaranteed. It could onlybe implemented if the provision of “security” declared in the constitution. Inthis conception, a political reform of law should be implementation of nationalgoals and objectives. Hence the law resulting from legislative mechanismcan be nationally applied, not overlapping, hierarchy arrangement, andfocused to the constitution. However, if any legislation that deviates, it shouldbe in the framework of implemented national goals. So strongly needed toformulate a grand design to make political law legislation has a cleardirection and acceleration for realizing welfare state. Due the politic of lawis really political policy that determines what legal rules should applyregulates in social and state living.